Beginnings and development of English teaching in the medical university - Trinidad Atiés Caballero; Susana García Buchaca; Vladimir González Fernández; Liana García Pérez; Ramona Vega Ramírez (Medisur)
Various authors have claimed the imperious necessity and significance of the acknowledgement and domain of the English language as a cultural means and way of communication among men. The present study aims an approximation to the teaching of this language in its diverse stages, starting from its beginnings up to its present situation in the Cuban Medical School. Here are stated the different approaches and methods that have engulfed the English teaching and its relations with the pedagogical and theoretical conceptions that have emerged, along with the criteria and judgments of the ones who dedicated their works to this field. Taking into consideration that the various pedagogical theories, the educational systems, the organization, the content and the teaching methods are determined by the conditions of the society's material life, whose development is influenced at a time; a revision and valorization of these conditions in different societies are carried out, as an important cause of the different pedagogical theories, methods and teaching approaches applied in the different schools, for example, in the Cuban Medical University.